Keragaman Suara Tonggeret dan Jangkrik di Taman Nasional Gunung Gede Pangrango: Sound Variety of Cicada and Cricket at Gunung Gede Pangrango National Park - Gautama Simanjuntak, Juniarto; Putri Amelya, Mega; Nuraeni, Fitri; Raffiudin, Rika (Departemen Biologi, Institut Pertanian Bogor, 2020)
Indonesia is a biodiversity country and has much of samples of bioacoustics but there are no bioacoustics data collected and saved to be referred. Bioacoustics is a study of frequency range, sound amplitudo intensity, sound fluctuation, and sound patterns. It is very useful to study more about population presumption and species determination. This insect bioacoustics research is done at Gunung Gede Pangrango National Park and aims to analyse variety of sound frequency of cicada and cricket. Methods which are used are recording the sounds, editing and analyzing the record result with Praat and Raven Lite 2.0 softwares, and analysing the environment. Analysing the sounds which is done is to find miximum frequency, minimum frequency, and average frequency. The result of the sounds analysis is compared to database in Singing Insect of North America (SINA). Environmental analysing includes temperature, air humidity, and light intensity. There are nine cicada sound recording files and twenty four cricket sound recording files. Cicada has high sound characteristic (9,168.2 Hz) and cricket has low sound characteristic (3,311.80 Hz). Comparation to Singing Insect of North America (SINA) database shows that the cicada’s sound is resemble to Tibicen marginalis and the cricket’s sound is resemble to Grylodes sigillatus.